PEMBERDAYAAN EKONOMI MASYARAKAT DESA SAMPE RAYA MELALUI EDUKASI MENABUNG DAN PEMASARAN DIGITAL UMKM - Tanjung, Nurdelima; Siti Aisyah; Tia Fatma Sari; Rosa Nurmeliana; Annisa Putri nazhiha (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2025)
This article discusses a community economic empowerment program in Sampe Raya Village thru early savings education and digital marketing training for MSMEs. The program aims to improve financial literacy, handicraft skills, and digital capabilities of the village community. The approach used includes interactive education, hands-on practical training, and ongoing mentoring, involving various relevant stakeholders. Initial results show improved financial literacy understanding, creativity in crafting, and digital marketing skills among villagers. The implementation of this strategy is expected to strengthen the financial foundation of families and open up wider market access, thereby sustainably improving the welfare and economic independence of the community in the digital age